NILAI-NILAI PENDIDIKAN ISLAM PADA KISAH NABI IBRAHIM - Hasan, Zainol (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
Merging two Methods between lecturing and Group Investigation ar Al-Quran is essentially dedicated to mankind wherever they are. One method to bring the Quran closer to human is through the stories that are presented in Al-Quran. This paper would like to investigate more about how the description of the Ibrahim story and its relevance to the values of Islamic education. The results found the data of the verses relating to the story of the prophet Ibrahim AS, as many as 186 verses spread in 25 surah. FromÂ  25 surah there are 17 (seventeen) surah down in Mecca, and 8 (eight) surah down in Medina. Furthermore, the values of Islamic education contained in the story of Prophet Ibrahim AS consists of the first; the value of uluhiyah, namely the values of faith and the values of worship; the value of uluhiyah is the value that God offers through his rasul who are immortal and never changed; it is fundamental and contains absoluteness for human life. Secondly, the values of humanity, namely the values that come from human beings, that is grown by human agreement, lived and thrived in human civilization. It is dynamic and contains truth that is relative and limited by space and time. In the Islamic context, human values can be identified with moral values. These values are honesty (shiddiq), trustworthiness (amanah), truth-telling (tabligh), intelligence (fathanah), love, patience, exemplary, and democracy.